A CERVICAL PAP SMEAR CYTOLOGY PATTERN OBSERVED IN AN INDIAN TERTIARY CARE HOSPITAL: A RETROSPECTIVE CROSS-SECTIONAL STUDY. - Raj, Anand; Haider, Md. Zeeshan; Prasad, Krishna Murari; Kumar, Roushan (Student's Journal of Health Research Africa, 2023)
Objective The objective of this study is to ascertain the prevalence of carcinoma cervix, non-neoplastic lesions, and premalignant lesions among patients exhibiting diverse clinical manifestations in the gynaecology outpatient setting. Materials and Methods The current investigation entailed a retrospective cross-sectional analysis of cervical smears obtained from individuals aged 21 years or above, with a study duration spanning one year. The conventional Pap smears underwent analysis, and the subsequent findings were duly documented. Results Out of the 1200 cases with satisfactory smears that were examined, 800 of them showed benign and inflammatory lesions, while 400 cases displayed epithelial lesions, which included premalignant and malignant lesions. Among a group of 400 individuals demonstrating epithelial lesions, a category of 150 cases was identified as ASCUS. Furthermore, a relatively limited group which includes 90 cases was classified as AGUS or an AGC-NOS. Conclusion Cervical cancer stands as the foremost etiological factor contributing to mortality associated with cancer in the female population. However, the incidence of this condition can be mitigated through the implementation of routine pap smear examinations aimed at early identification. A simple and affordable screening method that may be easily carried out at the main medical facility is the Pap smear test. Recommendation Encourage the establishment and promotion of regular screening programs, especially targeting populations at higher risk. Emphasize the importance of routine Pap smear tests for women, stressing the potential benefits of early detection and treatment.